(untitled) (CIPEEX, 2024)
THIS STUDY ANALYZED THE RIGHT TO MENTAL HEALTH IN THE BRAZILIAN PRISON SYSTEM BETWEEN THE YEARS 2018 AND 2023. A COMPREHENSIVE REVIEW OF THE LITERATURE AND AN ANALYSIS OF POLICIES, PROGRAMS AND LIVING CONDITIONS IN THE COUNTRY’S PRISONS WERE CONDUCTED. THE RESULTS REVEALED A COMPLEX SITUATION, WITH ADVANCES IN EXPANDING ACCESS TO MENTAL HEALTH SERVICES, EARLY DIAGNOSIS OF MENTAL DISORDERS AND RECOGNITION OF THE IMPORTANCE OF THE TOPIC. HOWEVER, PERSISTENT CHALLENGES SUCH AS OVERCROWDING, VIOLENCE AND LACK OF COORDINATION BETWEEN AGENCIES WERE IDENTIFIED. IT IS CONCLUDED THAT IT IS ESSENTIAL TO ADOPT AN INTEGRATED APPROACH, INVOLVING DIFFERENT GOVERNMENT SECTORS, TO GUARANTEE RESPECT FOR HUMAN RIGHTS, THE PROMOTION OF MENTAL HEALTH AND THE EFFECTIVE REINTEGRATION OF PRISONERS INTO SOCIETY. THE COMPLEXITY OF THIS SCENARIO REINFORCES THE NEED FOR AN INTEGRATED APPROACH, INVOLVING NOT ONLY THE INSTITUTIONS OF THE PRISON SYSTEM, BUT ALSO THE HEALTH, EDUCATION, SOCIAL ASSISTANCE AND JUSTICE SECTORS. PROMOTING MENTAL HEALTH IN THE PRISON SYSTEM IS NOT JUST A MATTER OF FULFILLING RIGHTS HUMAN RIGHTS, BUT ALSO AN EFFECTIVE STRATEGY TO REDUCE CRIMINAL RECIDIVISM RATES AND TO BUILD A FAIRER AND SAFER SOCIETY. &NBSP; &NBSP;